Social Network Analysis: Type of Information and Characteristics of Its Delivery Regarding Helicobacter pylori in Korea - Chang Seok Bang; Gwang Ho Baik (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims: Current production of knowledge and distribution of data is frequently mediated by social media in the form of unstructured text data rather than classical newspaper or journal format. Management of Helicobacter pylori infection is an important issue in Korea. However, there has been no study on the characteristics of information regarding H. pylori consumed and distributed in the social media by general population. Materials and Methods: This study evaluated characteristics of social media data regarding H. pylori in Korea using semantic network analysis with Textom and NodeXL Pro (2015.8.11∼2016.8.11, Naver, Daum, Youtube, and Twitter searching). Results: Total collected data in the Textom analysis about '헬리코박터' was 10,061. TF-IDF (term frequency × inverse document frequency) was as follows: ‘위암’, ‘위’, ‘감염’, ‘윌’, ‘균’, ‘치료’, ‘위궤양’, ‘원인’, ‘프로젝트’, ‘음식’, ‘세균’, ‘검사’, ‘예방’, ‘증상’, ‘건강’, ‘약’, ‘효과’. In the Twitter analysis, 96 nodes and 120 edges, and 86 unique edges were detected, suggesting low distribution of data. Misinformed data such as ‘헬리코박터-파이로리’, ‘라는-바이러스때문에’, ‘헬리코박터-프로젝트’, ‘위궤양이나-위’, ‘점막-출혈을’, ‘비롯하여-각종’, ‘부종을-억제하고’, ‘치료하는데-효과가’, ‘있습니다-또한’, ‘장티푸스-이질’, ‘등-전염성’, ‘세균이나-장’, ‘속의-세균들을’, ‘억제하는-효과가’, ‘프로젝트-윌’ were found. The most viewed movie in the Youtube analysis was ‘한국야쿠르트 헬리코박터 프로젝트 윌 그 한입을 경계하라_15초’ (210,577). Conclusions: Relative insufficiency, low distribution, and some misinformed data were found in some part of social media. Participation of healthcare professional is warranted to solve these issues.